This research examines photograp Color as a Communicator of Emotional Messages: A Symbolic Analysis in Sunset Photography - Kika, Rizkika Aulia; Abidin, Zainal (fakultas Desain Komunikasi Visual, 2025)
This research examines photography as a medium to visualize emotions through a symbolic approach and creative movement techniques within sunset portraiture. Employing a qualitative descriptive method and a phenomenological approach, this study explores how visual elements such as color, light, texture, composition, and movement are capable of representing complex emotions, including loneliness, self-reflection, and acceptance. The findings indicate that creative movement techniques amplify visual dynamics and establish an emotional connection between the artwork and the audience. Each visual element functions not only for aesthetic appeal but also as a symbol that non-verbally conveys emotional and philosophical messages. These results affirm the role of photography as a visual communication medium capable of deeply transmitting inner experiences.The study concludes that color in sunset photography functions as a strong visual element capable of conveying emotional messages through nonverbal communication mechanisms. Drawing upon Roland Barthes' semiotic framework, the analysis shows that the colors present in the sunset gradient operate not only at the denotative level as an observable natural phenomenon but also at the connotative level as culturally and personally embedded symbols that evoke emotional associations. The findings reveal that warm colors like orange and red elicit feelings of warmth, longing, and hope, while darker hues such as purple and deep blue evoke meanings related to contemplation, solitude, and introspection. This interpretation is reinforced by insights from interviews with Fitrian, who emphasizes that visual elements including color, composition, creative movement techniques, and lighting are intentionally constructed by the photographer to guide the audience’s perception and emotional interpretation.